The Influence Of Working Capital On Profitability In Pharmaceutical Sub-Sector Companies On The Stock Exchange Indonesia 2018-2022 - Ismi Aulia Rahma Ramly; A. Ifayani Haanurat; Nurlina, Nurlina (International Journal of Economic Research and Financial Accounting, 2024)
This research is a type of quantitative research with the aim of determining the effect of working capital on profitability in pharmaceutical sub-sector companies on the Indonesian stock exchange in 2018-2022. This study uses secondary data, namely annual financial statements on pharmaceutical sub-sector companies in 2018-2022.  The data analysis technique used is simple linear regression analysis. The sampling method is purposive sampling with a sample of 8 companies obtained from the Indonesia Stock Exchange. Based on the results of the analysis obtained, it is stated that working capital has a positive and significant effect on profitability, it is proven that t-calculation is greater than t-table, namely 2,060 > 2,028 and significance value (Sig.) 0.047 < 0.05, then H0 is rejected and H1 is accepted.